An insight into a combined effect of backsheet and EVA encapsulant on field degradation of PV modules - Buerhop, Claudia; Pickel, Tobias; Stroyuk, Oleksandr; Hauch, Jens; Peters, Ian Marius (Energy Science and Engineering, 2023)
Polymer components, in particular, backsheets (BSs) and ethylene-vinyl acetate (EVA) encapsulants, play a crucial role in the degradation of commercial silicon photovoltaic (PV) modules. Degradation mechanisms depend in a complex way on the composition and properties of all involved polymers. In this study, we demonstrate that differences in the composition of EVA encapsulants, in particular, the presence of additives, such as UV blockers, affect the degradative processes in a decisive way, even for modules with identical BSs. A combination of spectral, imaging, and electrical characterization techniques applied in a mixed lab/field study showed that the field aging of PV modules with the same BSs and different encapsulant components results in the development of different degradation signs, such as insulation resistance loss, corrosion of metal interconnects, water ingress, oxidation depth in the encapsulant, and potential-induced degradation, depending on the presence of additives in the encapsulant. The present study provides an outlook on the complex influence of polymer components on the lifetime and performance of silicon PV modules.
CRIS-Team Scopus Importer:2023-09-22
Keywords: energy systems; life cycle analysis; photovoltaics; solar energy